2016
DOI: 10.1080/08923973.2016.1184680
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced immune response to foot-and-mouth disease vaccine by oral administration of ginseng stem-leaf saponins

Abstract: Vaccination is an important approach to the control of foot-and-mouth disease (FMD). This study evaluated the effect of oral administration of ginseng stem-leaf saponins (GSLS) on the immune response to FMD vaccine and the gut mucosal immunity in mice. In experiment 1, mice were orally administered GSLS or not treated as a control. The animals were then immunized twice with FMD vaccine. Blood was sampled weekly within five weeks after the boost immunization for measurement of serum IgG and the isotypes. In exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 42 publications
3
15
0
Order By: Relevance
“…[5][6][7] Medicinal extracts from various traditional herbs have been extensively used as adjuvants with the aim of improving the protective immunity conferred by vaccines against viral diseases. 8,9,13,[19][20][21][22] In the present study, we demonstrated that GSLS and Se (in the form of sodium selenite) have an adjuvant effect and that combined administration of GSLS and Se stimulates significantly enhanced immune responses than does GSLS or Se used alone. Following oral administration of GSLS, mice that received aPrV vaccine diluted in Se-containing PSS provoked a significantly stronger gB specific serum antibodies response (IgG, IgG1 and IgG2a) and evidenced increased lymphocyte proliferation and cytolytic activity of NK cells along with higher production of cytokines (IL-12, IFN-γ, IL-5 and IL-10) by splenocytes.…”
Section: Gsls and Se Confer Protection To Mice Challenged With Lethsupporting
confidence: 53%
See 4 more Smart Citations
“…[5][6][7] Medicinal extracts from various traditional herbs have been extensively used as adjuvants with the aim of improving the protective immunity conferred by vaccines against viral diseases. 8,9,13,[19][20][21][22] In the present study, we demonstrated that GSLS and Se (in the form of sodium selenite) have an adjuvant effect and that combined administration of GSLS and Se stimulates significantly enhanced immune responses than does GSLS or Se used alone. Following oral administration of GSLS, mice that received aPrV vaccine diluted in Se-containing PSS provoked a significantly stronger gB specific serum antibodies response (IgG, IgG1 and IgG2a) and evidenced increased lymphocyte proliferation and cytolytic activity of NK cells along with higher production of cytokines (IL-12, IFN-γ, IL-5 and IL-10) by splenocytes.…”
Section: Gsls and Se Confer Protection To Mice Challenged With Lethsupporting
confidence: 53%
“…Over the last few years, outbreaks of pseudorabies have been reported on farms that widely used attenuated live vaccine (Bartha‐K61), indicating that the vaccine does not provide effective protection against PrV infection in various regions of China . Medicinal extracts from various traditional herbs have been extensively used as adjuvants with the aim of improving the protective immunity conferred by vaccines against viral diseases . In the present study, we demonstrated that GSLS and Se (in the form of sodium selenite) have an adjuvant effect and that combined administration of GSLS and Se stimulates significantly enhanced immune responses than does GSLS or Se used alone.…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations